An Analytical Model for the Corrosion Risk of Water Alternating Gas Injection Wells in CO2 Enhanced Oil Recovery. Issue 7 (28th May 2018) - Wang, Zi Ming; Song, Guang‐Ling
Abstract: An analytical model is proposed to describe the corrosion risk profile of a well tube in water alternating gas (WAG) CO2 injection conditions based on the assumption that the drying process of the water layer on the inner wall of the well tube plays a crucial role in controlling corrosion. In this model, the fluid properties, the thermodynamic equilibrium of CO2 and water steam, and an empirical CO2 corrosion equation are systematically considered. The description by this model reasonably indicates that fast injection can decrease the corrosion risk and push the highest risk region to a deeper zone, while a longer drying time for a thicker water layer left on the well inner wall can lead to higher corrosion risk. It can also be deduced that the offshore WAG case is more aggressive than the onshore case and some mitigation strategies are suggested for reducing the corrosion risk. These should be helpful for corrosion management and leakage monitoring in the practical WAG CO2 injection. Abstract : CCS combined with EOR is a feasible way to reduce CO2 emission. However, CO2 leakage from injection systems can ruin the surrounding environments. A model is proposed to describe the corrosion risk of water alternating gas (WAG) CO2 injection wells. A fast CO2 injection and a thin water layer can reduce well corrosion. An offshore WAG CO2 injection well is more risky than the onshore case and the corrosion risk increases with increasing seafloor depth.